2016
DOI: 10.1128/mcb.01034-15
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exchange Protein Directly Activated by Cyclic AMP Isoform 1 in Energy Homeostasis: Regulation of Leptin Expression and Secretion in White Adipose Tissue

Abstract: h Epacs (exchange proteins directly activated by cyclic AMP [cAMP]) act as downstream effectors of cAMP and play important roles in energy balance and glucose homeostasis. While global deletion of Epac1 in mice leads to heightened leptin sensitivity in the hypothalamus and partial protection against high-fat diet (HFD)-induced obesity, the physiological functions of Epac1 in white adipose tissue (WAT) has not been explored. Here, we report that adipose tissue-specific Epac1 knockout (AEKO) mice are more prone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…However, in a similar study, Rapgef3 −/− mice develop severe obesity, increased respiratory exchange ratio and impaired glucose tolerance 33 . Adipose tissue-specific Rapgef3 knockout mice on a high-fat diet are also more prone to obesity, show increased food intake, reduced energy expenditure, impaired glucose tolerance, and reduced circulating leptin levels 72 . More research is needed to understand the consequences of RAPGEF3 manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a similar study, Rapgef3 −/− mice develop severe obesity, increased respiratory exchange ratio and impaired glucose tolerance 33 . Adipose tissue-specific Rapgef3 knockout mice on a high-fat diet are also more prone to obesity, show increased food intake, reduced energy expenditure, impaired glucose tolerance, and reduced circulating leptin levels 72 . More research is needed to understand the consequences of RAPGEF3 manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that EPAC1 plays an important role in regulating adiposity and energy balance by modulating leptin signaling. A subsequent report using WAT-specific knockout EPAC1 mice further reveals EPAC1 engaging dual roles in leptin signaling, promoting leptin expression and secretion in peripheral WAT and suppressing leptin signaling in the CNS (444). The regulatory effects of EPAC on leptin signaling in the hypothalamus is most likely mediated by the small GTPase Rap1, as loss of neuronal Rap1 also protects against diet-induced obesity, glucose imbalance, and insulin resistance in the periphery while enhancing leptin sensitivity in hypothalamus (489).…”
Section: The Hypothalamic-pituitary-adrenal Axismentioning
confidence: 95%
“…Activation of Epac1 by cAMP further triggers down-stream RAS superfamily small GTPases, Rap1 and Rap2, which are critical for a wide variety of biological functions, ranging from cytoskeleton organization and intracellular trafficking to cell adhesion and junction789. Studies based on genetic Epac1 knockout mice have demonstrated that Epac1 contributes to leptin resistance1011, rickettsial infection12, chronic pain1314, stress induced phospholamban phosphorylation in cardiomyocytes15, Treg-mediated immune-suppression16, and cardiomyocyte hypertrophy17. However, the physiological roles of Epac1 in VSMC function and neointima formation remain controversial181920212223.…”
mentioning
confidence: 99%